Ischemic stroke as an initial presentation of neurosyphilis in a newly diagnosed HIV patient: A case report and literature review - Moaz O. Moursi (17019030) (2024)
Key Clinical Message With syphilis resurgence, physicians should be more vigilant to infection‐induced cerebral vasculitis in high‐risk patients presenting with neurological symptoms. In this case, neurosyphilis should not be missed. Thorough serologic screening and lumbar puncture are crucial for diagnosis, and further research is needed for safe and effective treatments in these populations. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ccr3.8794